The Political Situation in Armenia in 1920 and in 2018 after the Power Shift (comparative analysis) - Makaryan, Lilit (History and Culture, 2021)
Turkey was preparing to attack the Republic of Armenia in 1920. M. Kemal realized that Russia also had a plan to conquer Transcaucasia, and the division of Transcaucasia between Turkey and Russia seemed more realistic. Turkey had been occupying the internationally recognized territories of the Republic of Armenia since September 1920. According to the US President W. Wilson’s Arbitral Award, 90000 sq. km area of Western Armenia would be given to the Republic of Armenia. Russia set the task to sovietize the region and establish the Soviet regime in the East with Turkey’s support.Turkey tried to accomplish its unfinished programs in the region in April 2016, encouraging Azerbaijan to launch military operation against Artsakh, which failed. The power shift in Armenia in 2018 put Turkey in favorable conditions: the society became disunited, incomepetent officials were appointed to responsible positions, the highest ranking army officers were persecuted, obvious failures took place in foreign relations. The Covid-19 pandemic, which has been spreading in the region since 2020, placed Armenia under a complete external blockade and thus provided Turkey with new opportunities for its hostility programs.
Keywords: Soviet; power shift; region; war; pandemic